High-Energy-Level Blue Phosphor for Solution-Processed White Organic Light-Emitting Diodes with Efficiency Comparable to Fluorescent Tubes - Wang, Shumeng; Zhao, Lei; Zhang, Baohua; Ding, Junqiao; Xie, Zhiyuan; Wang, Lixiang; Wong, Wai-Yeung (iScience, 2018)
A high-energy-level blue phosphor FIr-p-OC8 has been developed for solution-processed white organic light-emitting diodes (WOLEDs) with comparable fluorescent tube efficiency. Benefiting from the electron-donating nature of the introduced alkoxy, FIr-p-OC8 shows not only efficient blue light but also elevated highest occupied molecular orbital/lowest unoccupied molecular orbital levels to well match the dendritic host H2. Consequently, the hole scattering between FIr-p-OC8 and H2 can be prevented to favor the direct exciton formation on the blue phosphor, leading to reduced driving voltage and thus improved power efficiency. By exploiting this approach, a maximum power efficiency of 68.5 lm W−1 is achieved for FIr-p-OC8-based white devices, slightly declining to 47.0 lm W−1 at a practical luminance of 1,000 cd m−2. This efficiency can be further raised to 96.3 lm W−1 @ 1,000 cd m−2 when a half-sphere is applied to increase light out-coupling. We believe that our results can compete with commercial fluorescent tubes, representing an important progress in solution-processed WOLEDs. [Display omitted] •High-energy-level blue phosphor FIr-p-OC8 is developed by alkoxyl substitution•Matched HOMO levels between dendritic host and blue-emitting dopant•Free of hole scattering to promote direct exciton formation on blue phosphor•Record-high power efficiency of 96.3 lm W−1 at 1,000 cd m−2 for solution-processed WOLEDs Organometallic Chemistry; Inorganic Materials; Optoelectronics